Fabrication and electrochemical performance of unprecedented POM-based metal–carbene frameworks. Issue 34 (11th August 2017) - Zhu, Pei-Pei; Sheng, Ning; Li, Meng-Ting; Li, Ji-Sen; Liu, Guo-Dong; Yang, Xi-Ya; Sha, Jing-Quan; Zhu, Meng-Liang; Jiang, Jianzhuang
Abstract : Unprecedented 3D POM-based MCFs showing good potential as anode materials in LIBs have been successfully fabricated for the first time. Abstract : Unprecedented polyoxometalate based metal–carbene frameworks (POM-based MCFs) [Cu10 (H3 trz)4 (Htrz)4 ](HPW12 O40 ) (1 ) and [Cu10 (H3 trz)4 (Htrz)4 ](H2 SiW12 O40 ) (2 ) have been fabricated via a hydrothermal reaction between 1, 2, 4-triazole and Cu(CH3 COO)2 with the saturated Keggin polyoxoanion [PW12 O40 ] 3− /[SiW12 O40 ] 4− as a template for the first time. Single crystal X-ray diffraction analysis reveals the successful encapsulation of Keggin POMs into the three-dimensional POM-based MCFs with lvt-a topology based on their effective coordination with Cu ions. Interestingly, these novel 3D POM-based MCFs exhibit good electrochemical performance in lithium-ion batteries (LIBs) as anode materials, with first discharge capacities of ca. 1620 and 1245 mA h g −1 for1 and2, respectively, at a current density of 100 mA g −1, and stabilized discharge capacities of ca. 570 mA h g −1 for1 and 426 mA h g −1 for2 after 100 cycles. This, in combination with their high thermal stability, suggests their good LIB application potential.